CITIZEN LAWSUIT: PELINDUNG HAK KONSTITUSIONAL DALAM SISTEM HUKUM INDONESIA - Ismantara, Stefany (JOURNAL EQUITABLE, 2023)
The 1945 Constitution established constitutional rights for citizens and emphasized the need for public participation to safeguard these rights. Citizen lawsuits serve as a form of public participation, but the absence of a legal basis in Indonesia has created uncertainty in their implementation. This study aims to examine the mechanism of citizen lawsuits within the Indonesian legal system, presenting it as a juridical alternative for protecting citizens' constitutional rights. The author utilized a normative legal research method with a qualitative and case-based approach through literature review. Citizen lawsuits enable citizens to take legal action against state officials who have neglected their rights. Courts have relied on jurisprudence and guidelines for handling environmental cases, such as the Chief Justice of the Supreme Court of the Republic of Indonesia Decree Number 36/KMA/SK/II/2013. Unlawful acts falling under the executive's jurisdiction serve as the subject of citizen lawsuits. Research on various citizen lawsuit cases demonstrates their effectiveness in defending citizens' constitutional rights. However, financial and knowledge limitations pose obstacles. Financial challenges can be addressed through community collaborations, pooling resources. To overcome knowledge limitations in filing citizen lawsuits, a dedicated regulation outlining the mechanism should be established.